Localised corrosion assessement of crambe-oil-based polyurethane coatings applied on the ASTM 1200 aluminum alloy - Nardeli, J. V. [UNESP]; Snihirova, D. V.; Fugivara, C. S. [UNESP]; Montemor, M. F.; Pinto, E. R.P. [UNESP]; Messaddecq, Y. [UNESP]; Benedetti, A. V. [UNESP] (Elsevier, 2016)
Coatings composed of polyurethanes derived from polyesters of crambe oil and pre-polymer obtained from hexamethylene diisocyanate and castor oil were prepared (1:2 and 1:3, respectively) and applied on the Al alloy 1200. The corrosion resistance of the coated panels was studied by linear polarization and conventional electrochemical impedance (EIS). The fraction of an active area of the substrate was around 0.017% and 0.013% for the 1:2 and 1:3 coatings, respectively. The performance of pristine samples was also studied by electrochemical impedance spectroscopy. An artificial scratch was performed on pristine samples and the local corrosion activity was studied by localized impedance spectroscopy (LEIS) and scanning vibrating electrode technique (SVET) in NaCl solutions. Filiform corrosion was observed for the panel coated with the modified polyester and pre-polymer 1:3 after 12 h of test. The scratched sample of modified polyester and pre-polymer 1:2 showed better performance in NaCl solution and the coating seems to present a self-healing response to the artificial damage.
Keywords: Aluminium alloy; EIS, SEM, Polymer coatings; Organic coatings; Scratching electrode